Hubungan Pengetahuan Dengan Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri Di SMP N 1 Karangnongko - Astri Wahyuningsih; Wiwin Rohmawati (Universitas Muhammadiyah Klaten, 2020)
Anemia is a major nutritional problem in Indonesia, especially iron deficiency anemia. Anemia has a serious impact on adolescents. It is very important to overcome anemia in adolescent girls so that the problem of anemia does not continue during pregnancy, one of which is by consuming a blood supplement tablet (TTD) containing 60 mg of elemental iron and 400 mcg of folic acid. Efforts to overcome anemia in adolescents include increasing knowledge to increase compliance with iron tablets. This study aims to determine the relationship between knowledge and adherence to blood-supplemented tablet consumption in young girls at SMP N 1 Karangnongko The research method used was descriptive correlation with cross sectional approach. The respondents used in this study were young girls at SMP N 1 Karangnongko with a purposive sampling technique based on inclusion and exclusion. The instruments used were questionnaires for knowledge and monitoring forms for teenage girls' iron supplement program in schools. For compliance. The data were analyzed using the Chi Square test with the result that there is a relationship between knowledge and compliance with blood-added tablet consumption at SMP N 1 Karangnongko with p value = 0.001 (p <0.05). The conclusion of this study is that there is a relationship between knowledge and compliance with blood-supplemented tablet consumption at SMP N 1 Karangnongko. Suggestions for young women to add insight about blood-supplemented tablets and increase compliance in consuming blood-supplemented tablets so that they don't have anemia..